1981
DOI: 10.1007/bf01658293
|View full text |Cite
|
Sign up to set email alerts
|

Stress ulcer disease in the burned patient

Abstract: Stress-induced ulcers of the stomach and duodenum in massively burned patients, otherwise known as Curling's ulcers, result from a defect in the mucosal barrier to secreted acid. The etiology of this defect is related, at least in part, to mucosal ischemia, which is aggravated by hypotension, sepsis, and hypoxia. Early prophylactic administration of antacids and cimetidine, either singly or in combination, has significantly reduced the occurrence of the lifethreatening complications of these lesions. When prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Gastric ulcers are small, sharply demarcated and superficial. Duodenal ulcers tend to be single, deeper and more prone to perforate [2,3,4,5]. Ninety years after Curling’s report, Cushing [6] identified trauma or surgery of the central nervous system as a stimulating trigger for a specific form of stress ulcer that bears his name.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric ulcers are small, sharply demarcated and superficial. Duodenal ulcers tend to be single, deeper and more prone to perforate [2,3,4,5]. Ninety years after Curling’s report, Cushing [6] identified trauma or surgery of the central nervous system as a stimulating trigger for a specific form of stress ulcer that bears his name.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated studies have shown the effectiveness of antacids in preventing this lesion [52,53]. The early reports of the ineffectiveness of H2 recep-' tor antagonists may be attributed to inadequate dosage, although there are still conflicting reports about their efficacy [54,55]. Prostaglandins have not been demonstrated to be an effective prophylaxis against hemorrhagic gastritis [56].…”
Section: Medical Therapymentioning
confidence: 96%
“…Gastric antral or duodenal lesions did not occur without concomitant ulcers or erosions in the gastric fundus [16]. Simultaneous gastric and duodenal stress ulcers occur in 15% of burn patients [35]. Autopsy series in burn patients showed that isolated duodenal stress ulcers can occur [11,17,21,22].…”
Section: Clinical Presentation and Coursementioning
confidence: 99%
“…Stress ulcers are most often multiple and located in the gastric fundus or proximal stomach [28,34,35]. One endoscopic survey of burn patients noted mucosal lesions were predominant in the gastric fundus and body.…”
Section: Clinical Presentation and Coursementioning
confidence: 99%